Signs and symptoms from ectodermal organs in young Swedish individuals with oligodontia - B. BERGENDAL, J. NORDERYD, M. BÅGESUND, & A. HOLST (Paediatric Dentistry, 2006)
The aim was to assess signs and symptoms from other ectodermal organs in addition to teeth in young individuals with oligodontia and to establish the prevalence of oligodontia.